Pictures and repeated exposure increase perceived accuracy of news headlines. Issue 5 (10th May 2020) - Smelter, Thomas J.; Calvillo, Dustin P.
Summary: Fake news, deliberately inaccurate and often biased information that is presented as accurate reporting, is perceived as a serious threat. Recent research on fake news has documented a high general susceptibility to the phenomenon and has focused on investigating potential explanatory factors. The present study examined how features of news headlines affected their perceived accuracy. Across four experiments (total N = 659), we examined the effects of pictures, perceptual clarity, and repeated exposure on the perceived accuracy of news headlines. In all experiments, participants received a set of true and false news headlines and rated their accuracy. The presence of pictures and repeated exposure increased perceived accuracy, whereas manipulations of perceptual clarity did not show the predicted effects. The effects of pictures and repeated exposure were similar for true and false headlines. These results demonstrate that accompanying pictures and repeated exposure can affect evaluations of truth of news headlines.